Why is Production More Volatile than Sales? Theory and Evidence on the Stockout-Avoidance Motive for Inventory-Holding - Kahn, J. A. (Quarterly Journal of Economics, 1992)
This paper argues that the macroeconomically interesting features of inventory behavior are well captured by a model in which firms face only demand uncertainty with a nonnegativity constraint on inventories. Empirical implications of the "stockout-avoidance" model of inventory behavior are derived and then tested on disaggregated automobile industry data. The results largely support the model, though they suggest a small role for production-smoothing as well. Subsidiary evidence on the relative variance of demand and cost shocks suggests that demand shocks are indeed more important.